1998
DOI: 10.1161/01.cir.98.16.1610
|View full text |Cite
|
Sign up to set email alerts
|

Oral Delivery of Anticoagulant Doses of Heparin

Abstract: Background-Parenteral heparin is the anticoagulant of choice in hospitalized patients. Continued anticoagulation is achieved by subcutaneous administration of low-molecular-weight heparin or with an orally active anticoagulant such as warfarin. An oral heparin formulation would avoid the inconvenience of subcutaneous injection and the unfavorable drug interactions and adverse events associated with warfarin. A candidate delivery agent, sodium N-[8(-2-hydroxybenzoyl)amino]caprylate (SNAC), was evaluated with es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…A randomized, double-blind, controlled study performed in humans to study the safety and the effect of heparin/SNAC in anticoagulation showed that heparin/SNAC increased the coagulation parameters (APTT, anti-FIIa and FXa, and tissue factor pathway inhibitor) and, that neither heparin or SNAC alone changed these parameters [ 77 ]. A major limitation seems to be heparin high first pass metabolism by heparinase in the liver after GI absorption.…”
Section: Co-administration With Penetration Enhancersmentioning
confidence: 99%
“…A randomized, double-blind, controlled study performed in humans to study the safety and the effect of heparin/SNAC in anticoagulation showed that heparin/SNAC increased the coagulation parameters (APTT, anti-FIIa and FXa, and tissue factor pathway inhibitor) and, that neither heparin or SNAC alone changed these parameters [ 77 ]. A major limitation seems to be heparin high first pass metabolism by heparinase in the liver after GI absorption.…”
Section: Co-administration With Penetration Enhancersmentioning
confidence: 99%
“…In some circumstances, such as inflammatory diseases of the lung, local administration of heparin by inhalation is an option, but where systemic effects are required, an efficient and predictable drug absorption profile becomes necessary. Absorption of unmodified, unfractionated, and LMW heparins has been reported following oral administration in rats [154–156], and in rats and humans when administered with the absorption-enhancing delivery agent sodium N-[8(2-hydroxybenzoyl)amino]caprylate (SNAC) [157160]. Similarly, augmentation of heparin absorption via the pulmonary [161167] and nasal [168170] routes has been described, when the drug is coadministered with delivery systems including polyethyleneimines, cyclodextrins, alkylmaltosides, alkanoylsucroses, poly-L-arginine, and within PEGylated nanocarriers.…”
Section: New Approaches To Treatmentmentioning
confidence: 99%
“…PEs have been successfully applied to the development of oral dosage forms of various biopharmaceuticals including heparin, insulin, calcitonin, parathyroid hormone, and growth hormone, all of which are advancing through clinical trials (Lee et al ., 1994; Baughman et al ., 1998; Nissan et al ., 2000; Leone-Bay et al ., 2001; Buclin et al ., 2002; Goldberg and Gomez-Orellana, 2003; Kidron et al ., 2004). Accordingly, numerous potential PEs have been identified including surfactants, fatty acids and their derivatives, bile acids, cyclodextrins, etc (Whitehead et al ., 2008b).…”
Section: Introductionmentioning
confidence: 99%